2005
DOI: 10.1620/tjem.207.33
|View full text |Cite
|
Sign up to set email alerts
|

Fibrin Stimulates the Proliferation of Human Keratinocytes through the Autocrine Mechanism of Transforming Growth Factor-.ALPHA. and Epidermal Growth Factor Receptor

Abstract: In the field of dermatology and plastic and reconstructive surgery, fibrin gel is regarded as a material that promotes wound healing. To test the hypothesis that fibrin may promote the growth of the epidermis, we examined its effects on the proliferation of cultured keratinocytes. Human keratinocytes were cultivated in fibrincoated wells, and the cell numbers and transforming growth factor (TGF)-α , secreted into the cultured medium, were measured. We also assessed the capacity of epidermal growth factor recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 24 publications
3
9
0
Order By: Relevance
“…Similarly, we have confirmed that the primary effect of fibrin adhesive is to prevent run‐off even when using the diluted concentrations of fibrinogen and thrombin that are optimal for metabolic activity. Nevertheless, our findings also provide support for the theory that fibrin adhesive stimulates keratinocyte proliferation (Figures 5 and 6) and this concurs with recent reports from other groups 25,26 . We thus look forward to seeing further evaluation of our optimized procedure in animal and clinical trials.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, we have confirmed that the primary effect of fibrin adhesive is to prevent run‐off even when using the diluted concentrations of fibrinogen and thrombin that are optimal for metabolic activity. Nevertheless, our findings also provide support for the theory that fibrin adhesive stimulates keratinocyte proliferation (Figures 5 and 6) and this concurs with recent reports from other groups 25,26 . We thus look forward to seeing further evaluation of our optimized procedure in animal and clinical trials.…”
Section: Discussionsupporting
confidence: 92%
“…In keratinocytes, fibrin stimulated the autocrine production of transforming growth factor alpha through the epidermal growth factor receptor. 47 Fibrin also partially restored the ability of senescent and growth-arrested human dermal fibroblasts to continue replicating. 48 However, after 2 weeks of cell cultivation, the cell proliferation (measured by cell metabolic activity) on membranes with fibrin became similar to the cell proliferation on the nonmodified membranes, which probably correlated with the degree of fibrin degradation.…”
mentioning
confidence: 93%
“…However, after eight days of postinjury, patients with sepsis, large TBSA and non-survivors have had significantly lower values than those of non-septic, low TBSA and survivor group. Topical application of TGFα accelerates epidermal regeneration of partial thickness burn [51]. The burn-induced inflammation and inflammatory cytokines cause insulin resistance and hyperglycemia that are reflected on organ functions including liability to infection.…”
Section: Discussionmentioning
confidence: 99%